Feasibility Analysis of the Chicken Holic Business - Dini Vientiany; Atika Safitri; Amelia Putri; Ika Salsabila; Muhammad Farhan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The culinary industry, particularly the fast-food sector based on chicken products, continues to experience significant growth in line with changes in modern lifestyles that prioritize practicality, affordability, and consistent taste. This study aims to examine the feasibility of Chicken Holic as a modern culinary business through a comprehensive business feasibility analysis. The research employs a descriptive qualitative approach by evaluating several key aspects, including market and marketing, legal, technical and operational, management, financial, halal and sharia compliance, as well as economic, social, and environmental aspects. The results indicate that Chicken Holic possesses strong market potential supported by a broad target market, clear product positioning, and the effective implementation of the marketing mix strategy (4P). From a legal perspective, the business operates under a limited liability company and has fulfilled essential business licensing requirements, including halal certification. Operationally and managerially, Chicken Holic is supported by an efficient organizational structure, well-designed operational layouts, and clearly defined standard operating procedures. Financial analysis shows that the business is feasible, with stable projected monthly profits and an estimated payback period of approximately 23–24 months. In addition to its financial viability, Chicken Holic contributes positively to job creation, local economic development, and the implementation of social and environmental responsibility. Overall, the findings confirm that Chicken Holic is a viable culinary business with strong potential for sustainable development.